The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.11114/jets.v4i6.1404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biblio group Counseling Supported with the Story of the Little Prince upon Mindfulness

Abstract: Using books for healing psychological health is becoming popular day by day. In this process bibliotherapy brings forward suggestions of psychological insight, relieving by identification, relieving from suppressed feelings by discharging and reflecting emotions. The aim of this research is to analyse the effect of biblio group counseling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…One of the strategies that exist in guidance and counseling services is biblio-counseling or biblio-therapy (Suvilehto et al, 2019). Biblio-counseling can be done individually or in groups (İlbay, 2016;Özen & Köksalan2i, 2019;Supriyanto & Wahyudi, 2018;Yontz-Orlando, 2017). By implementing biblio-counseling in groups, it can provide opportunities for students to be able to express feelings, conflicts and realize joy together (Fitzgerald, 2017;MacArthur & Mack, 2017;Tomlinson, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strategies that exist in guidance and counseling services is biblio-counseling or biblio-therapy (Suvilehto et al, 2019). Biblio-counseling can be done individually or in groups (İlbay, 2016;Özen & Köksalan2i, 2019;Supriyanto & Wahyudi, 2018;Yontz-Orlando, 2017). By implementing biblio-counseling in groups, it can provide opportunities for students to be able to express feelings, conflicts and realize joy together (Fitzgerald, 2017;MacArthur & Mack, 2017;Tomlinson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown how biblio-counseling can be used to help overcome problems such as mental health, obsessive compulsive disorder, unhappiness, and increase individual motivation (Heo & Cho, 2019;İlbay, 2016;Sevinç, 2019). Truancy behavior among junior high school students is very important to observe, because truancy behavior that occurs is a form of juvenile delinquency that can harm students, parents and schools.…”
Section: Introductionmentioning
confidence: 99%
“…In general, bibliocounseling and counseling share the same purpose, to assist students in obtaining the right learning motivation (Pardeck, 2014). It aims to solve problems associated with counselee (Csorba-Simon, 2014;lbay, 2016;Özdemir, 2016). Therefore, the purpose of bibliocounseling is highly dependent on the counselee's problem, and ability to overcome these complications (Akinola, 2014).…”
Section: Introductionmentioning
confidence: 99%